Identification of odorous constituents of southern yellow pine and China fir wood: the effects of extractive removal. Issue 18 (25th April 2018) - Liu, Ru; Wang, Chen; Huang, Anmin; Lv, Bin
Abstract : In this study, the odors of two types of softwood species, namely southern yellow pine ( Pinus spp.) and China fir ( Cunninghamia lanceolata (Lamb.) Hook.), were identified and extracted with ethanol–toluene for the removal of extractives. Abstract : In this study, the odors of two types of softwood species, namely southern yellow pine ( Pinus spp.) and China fir ( Cunninghamia lanceolata (Lamb.) Hook.), were identified and extracted with ethanol–toluene for the removal of extractives. The odorous components of neat and extracted wood were identified via gas chromatography-mass spectrometry/olfactometry (GC-MS/O). The results showed that about 40 key identified volatile compounds (peak area above 0.2%) were detected from the GC-MS data, and more than 50 kinds of odorants were identified using GC-O. The time concentrated on was from 15 to 33 min for GC-O, which was different to the time concentrated on for GC-MS. The amounts of both volatile compounds and odorants in pine were more than in fir. After extraction, the amounts and intensities of some odorants decreased, while some remained. However, the extraction process resulted in benzene residue and led to increased benzene odor.